PERAN KOMITE PENYELIDIKAN DAN PEMBERANTASAN KORUPSI KOLUSI DAN NEPOTISME (KP2KKN) JAWA TENGAH DALAM MENGAWASI KASUS TINDAK PIDANA KORUPSI DI JAWA TENGAH PERIODE TAHUN 2012 - Yohanes Ricky Basuki; Budi Setiyono; Lusia Astrika (Journal of Politic and Government Studies, 2014)
ABSTRACT This research was conducted with the aim that, to find out how Non -Governmental Organization ( NGO ) Committee of Inquiry Corruption and Collusion Nepotisne Central Java ( Central Java KP2KKN ), as an institution concerned in the eradication of corruption in the roles and functions of supervision, in addition to the also to know what are the factors supporting and inhibiting. This study focused on the period in 2012, the year in which there is something interesting, because an increase in the number of significant cases of corruption is so high in Central Java , when compared with previous years.This study uses qualitative descriptive refer - analitif, with data collection techniques using purposive sampling is taking on a data source with a certain consideration. The subjects in this study were all agency workers KP2KKN Central Java. While the collection and analysis of these data refer to interviews, observation, documentation , and data processing are obtained.These results indicate that KP2KKN Central Java in 2012 had engaged in the prevention of corruption act, monitoring, and to advocate against several alleged cases of corruption and that amounts to 215. While the cause of the significant increase in the number of cases in 2012 were caused by unresolved legal proceedings some cases from the previous year, then the legal process runs in 2012. Meanwhile it in carrying out its role as an anti -corruption NGO, they are have several obstacles, both internal and external organization. But there are several factors supporting the institution to survive.In the fight against corruption requires commitment and cooperation between Central Java KP2KKN with law enforcement agencies, such as police, prosecutors, courts, and correctional institutions in order to obtain optimal results in combating corruption. As they should be implemented in Article 13 of UNCAC, that "the State shall promote the active participation of individuals and groups outside the public sector, such as civil society, non- governmental organizations and community -based organizations, in anti - corruption activities”. Because these institutions are the state institutions should cooperate with NGOs like KP2KKN Central Java.Keywords : NGO, Monitoring, Corruption.